2016
DOI: 10.1016/j.addbeh.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 8-item Attitudes Towards Gambling Scale (ATGS-8) in a British population survey

Abstract: 5 6Introduction. Public opinions concerning gambling are an important factor in shaping public 7 policy. Little empirical attention has been given to assessing gambling attitudes within the general 8 population. The aim of the present study is to validate the 8-item Attitudes Towards Gambling 9Scale (ATGS-8) in British individuals and to investigate associations of these attitudes with 10 frequency of gambling and gambling problems. 11 Methods. Data were derived from 7746 individuals participating in the Briti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
(7 reference statements)
0
16
1
Order By: Relevance
“…Men aged 18–54 had a generally positive attitude in 2011, and by 2015 the age group 55–64 also took a positive view. Overall these results show a clear tendency towards more favourable gambling attitudes and towards a narrowing of gender differences – a major departure from earlier results in Finland, and from results in the UK and Australia [ 1 , 3 , 4 , 16 , 40 ].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Men aged 18–54 had a generally positive attitude in 2011, and by 2015 the age group 55–64 also took a positive view. Overall these results show a clear tendency towards more favourable gambling attitudes and towards a narrowing of gender differences – a major departure from earlier results in Finland, and from results in the UK and Australia [ 1 , 3 , 4 , 16 , 40 ].…”
Section: Discussioncontrasting
confidence: 81%
“…In many countries including Finland [ 1 ], Australia [ 2 ] and the UK [ 3 ], public attitudes towards gambling tend to be negative, more so among women than men [ 1 , 3 5 ]. Male gender as well as age between 18 and 54 have been found to correlate with more positive attitudes towards gambling [ 1 , 3 ], but some evidence indicates that age has no effect [ 6 ]. It has been reported that men and younger individuals typically gamble more and have a higher risk of developing gambling problems [ 7 – 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher scores indicate more positive attitudes towards gambling. Previous validations of this scale confirmed its one-dimensional structure, and good concurrent validity (Canale et al 2016b). For the present study, the instrument was translated and back translated to the Portuguese language.…”
Section: Attitudes Towards Gambling Scale (Atgs8 Wardle Et Al 2011)mentioning
confidence: 58%
“…ATGS‐8, a widely used measure in studies concerning gambling, comprises eight questions in total . The alpha reliability of the ATGS‐8 was acceptable (α = 0.75 for Sample 1 and α = 0.84 for Sample 2), and the scale ranged from 8 to 39 ( M = 23.41, SD = 5.09) in Sample 1 and from 9 to 40 ( M = 24.00, SD = 6.23) in Sample 2.…”
Section: Methodsmentioning
confidence: 99%